The effect of Ganoderma lucidum polysaccharide extract on sensitizing prostate cancer cells to flutamide and docetaxel: an in vitro study - Ramin Rahimnia; Mohmammad Reza Akbari; Alimohammad Fakhr Yasseri; Diana Taheri; Akram Mirzaei; Helia Azodian Ghajar; Parmida Dehghanpoor Farashah; Leila Zareian Baghdadabad; Seyed Mohammad Kazem Aghamir (Scientific Reports, 2023)
Abstract Ganoderma lucidum polysaccharide is the most widely used complementary therapy in cancer. The present study aims to investigate the possible interaction between Ganoderma lucidum polysaccharide and Docetaxel (a chemotherapy drug) and the first-line medication for prostate cancer treatment (Flutamide) and sensitizing the cells to these treatments. The cytotoxic effects of Ganoderma lucidum polysaccharide in combination with Docetaxel and Flutamide on prostate cancer cells were investigated by the MTT test, Hoechst staining, and flow cytometry. In addition, the expression of genes related to apoptosis, angiogenesis, Epithelial-Mesenchymal Transition pathway (EMT), and prostate cancer biomarkers by Real-Time PCR was investigated. The results demonstrated that IC50 values for Ganoderma lucidum polysaccharide (30 μM and 20 μM), Docetaxel (10 μM and 5 μM), and Flutamide (20 μM and 12 μM) with MTT were confirmed by flow cytometry in a dose and time-dependent manner. Regarding the high efficacy of Ganoderma lucidum polysaccharide in combination with Flutamide and Docetaxel, 10 μM and 5 μM Flutamide were used instead of 20 μM and 12 μM and 5 μM and 2 μM Docetaxel was used instead of 10 μM and 5 μM in PC3 and LNCap, respectively. Moreover, for the first time, it was shown that Ganoderma lucidum polysaccharide alone and in combination with Docetaxel and Flutamide significantly augmented apoptosis, reduced cell migration and colonization, and downregulated expression of KLK2 and EMT pathway genes in both PC3 and LNCap cell line (P < 0.01). Ganoderma lucidum polysaccharide synergistically increased the effect of Docetaxel and Flutamide and increased the sensitivity of the prostate cancer cell lines to these drugs. Therefore, it may provide a new therapeutic strategy against prostate cancer.